5-Fluoro-2-indolyl des-chlorohalopemide (FIPI), a Phospholipase D Pharmacological Inhibitor That Alters Cell Spreading and Inhibits Chemotaxis - Su, Wenjuan (American Society for Pharmacology and Experimental Therapeutics, 2009)
The signaling enzyme phospholipase D (PLD) and the lipid second messenger it generates, phosphatidic acid (PA), are implicated in many cell biological processes, including Ras activation, cell spreading, stress fiber formation, chemotaxis, and membrane vesicle trafficking. PLD production of PA is inhibited by the primary alcohol 1-butanol, which has thus been widely employed to identify PLD/PA-driven processes. However, 1-butanol does not always effectively reduce PA accumulation, and its use may result in PLD-independent deleterious effects. Consequently, identification of potent specific small-molecule PLD inhibitors would be an important advance for the field. We examine one such here, 5-fluoro-2-indolyl des-chlorohalopemide (FIPI), which was identified recently in an in vitro chemical screen for PLD2 inhibitors, and show that it rapidly blocks in vivo PA production with subnanomolar potency. We were surprised to find that several biological processes blocked by 1-butanol are not affected by FIPI, suggesting the need for re-evaluation of proposed roles for PLD. However, FIPI does inhibit PLD regulation of F-actin cytoskeleton reorganization, cell spreading, and chemotaxis, indicating potential utility for it as a therapeutic for autoimmunity and cancer metastasis.